1983
DOI: 10.1083/jcb.97.3.866
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and regulation of acute phase plasma proteins in primary cultures of mouse hepatocytes.

Abstract: Adult mouse hepatocytes respond in vivo to experimentally induced acute inflammation by an increased synthesis and secretion of al-acid glycoprotein, haptoglobin, hemopexin, and serum amyloid A. Concurrently, the production of albumin and apolipoprotein A-1 is reduced. To define possible mediators of this response and to study their action in tissue culture, we established primary cultures of hepatocytes. Various hormones and factors that have been proposed to regulate the hepatic acute phase reaction were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0
5

Year Published

1985
1985
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 31 publications
6
40
0
5
Order By: Relevance
“…This result suggests that the goldfish response occurs through reactions with NF-IL6 and IL6-RE consensus sequences in the promoter region (Kikuchi et al, 1997). Human hemopexin plasma levels also increase during acute infections, suggesting that its biosynthesis is subject to control mechanisms responsible for the acute-phase reaction (Baumann et al, 1983;Poli and Cortese, 1989). Thus, goldfish Wap65 could be considered as an acute-phase protein, like hemopexins.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that the goldfish response occurs through reactions with NF-IL6 and IL6-RE consensus sequences in the promoter region (Kikuchi et al, 1997). Human hemopexin plasma levels also increase during acute infections, suggesting that its biosynthesis is subject to control mechanisms responsible for the acute-phase reaction (Baumann et al, 1983;Poli and Cortese, 1989). Thus, goldfish Wap65 could be considered as an acute-phase protein, like hemopexins.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse hepatocytes were prepared by in situ retrograde perfusion of the liver of 10-week-old C57BL/6J male mice with collagenase. 3,57 The parenchymal cells were collected by differential centrifugation and showed viability Ͼ90%. The cells were plated into culture dishes coated with collagen (Vitrogen 100; Collagen Biomaterials, Palo Alto, CA) (1 ϫ 10 5 cells/cm 2 ) in Dulbecco' s modified Eagle medium containing 10% fetal calf serum, 4.5 g/mL glucose, penicillin, streptomycin, and gentamicin.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 However, the level of expression and cytokine regulation of individual APPs appears also to be additionally modulated by the action of endocrine hormones 3,4 and growth factors. [5][6][7] Few studies indicated a modest inhibitory effect of epidermal growth factor (EGF) on APPs in cultured hepatic cells.…”
mentioning
confidence: 99%
“…Decreased albumin synthesis is an integral part of the acute phase response, probably resulting directly from the effect of macrorhage-derived mediators on albumin synthesis;" 26 Albumin, together with a number of other transport proteins, has thus been called a negative acute phase reactant. This aspect of decreased albumin synthesis occurring in inflammation together with transfer to the extravascular pool is a major factor in complicating the interpretation of albumin levels due to other mechanisms.…”
Section: Inflammationmentioning
confidence: 99%